2011
DOI: 10.2166/wst.2011.450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microcystis aeruginosa on membrane fouling in a biologically treated effluent

Abstract: Microcystis aeruginosa was cultured in biologically treated municipal effluent to simulate blue-green algal bloom conditions in a treatment lagoon. The effect of algae in the early, mid and late phases of growth on membrane fouling, chemical coagulation (alum or aluminium chlorohydrate (ACH)) and hydraulic cleaning on the microfiltration of this effluent was investigated. The effect of M. aeruginosa in the early phase was negligible and gave a similar flux profile and permeate volume to that of effluent alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…AOM has been demonstrated to cause severe fouling for low-pressure polymeric [5][6][7][8] and ceramic membranes [9,10] as it contains a high proportion of high molecular weight (MW) biopolymers such as polysaccharides and proteinaceous substances which have been identified as the most problematic foulants for the membranes. Moreover, the blooms can lead to the release of harmful algal metabolites including toxins into the drinking water, posing a threat to human health [11].…”
Section: Introductionmentioning
confidence: 99%
“…AOM has been demonstrated to cause severe fouling for low-pressure polymeric [5][6][7][8] and ceramic membranes [9,10] as it contains a high proportion of high molecular weight (MW) biopolymers such as polysaccharides and proteinaceous substances which have been identified as the most problematic foulants for the membranes. Moreover, the blooms can lead to the release of harmful algal metabolites including toxins into the drinking water, posing a threat to human health [11].…”
Section: Introductionmentioning
confidence: 99%
“…The algal organic compounds are commonly dominated by hydrophobic proteins and hydrophilic polysaccharides which have been widely regarded as responsible for the significant fouling issues in membrane filtration processes [5]. It has been demonstrated that the presence of AOM associated with natural organic matter in surface water or effluent organic matter in wastewater can further reduce the flux of polymeric MF/UF membranes [6][7][8]. Some efforts have been made since to characterise the AOM fouling of the polymeric MF/UF membranes, with a view to understanding the fouling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…AOM comprises mainly high molecular weight (MW) organics such as protein-like and polysaccharide-like substances [5] which can cause severe membrane fouling and lead to decrease in membrane permeability [3,4]. It has been demonstrated that the presence of AOM in addition to the effluent organic matter in secondary effluent can further reduce the efficiency of LPM filtration [6,7], thus increasing the operating cost. However, Lee and Walker [8] reported that hydrophobic polysulfone UF membrane could remove 91% of microcystin-LR whereas hydrophilic CA membranes adsorbed little or no microcystin-LR.…”
Section: Introductionmentioning
confidence: 99%